2014
DOI: 10.1111/sji.12186
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Duodenal Biopsies and Whole Blood from Dogs with Food‐Responsive Chronic Enteropathy and Healthy Dogs with Toll‐Like Receptor Ligands and Probiotic Enterococcus faecium

Abstract: The composition of the microbiome plays a significant role in the pathogenesis of inflammatory bowel disease (IBD) in humans and chronic enteropathies (CE) in dogs. The administration of probiotic micro-organisms is one way of modulating the microbiome, but experiments elucidating mechanisms of action of probiotics in the intestine of healthy and CE dogs are lacking. The aim of our study was to investigate the effects of different Toll-like receptor (TLR) ligands and Enterococcus faecium (EF) on ex vivo cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 55 publications
2
23
0
Order By: Relevance
“…Our findings demonstrate that the Pam3CSK4 TLR2 agonist alone significantly increased the production of TNF-α as previously described [30, 31]. In agreement with the present study, stimulation of purified canine polymorphmononuclear cells (PMNs) with lipoteichoic acid, a ligand of TLR2, promoted the release of pro-inflammatory chemokine IL-8 [32].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings demonstrate that the Pam3CSK4 TLR2 agonist alone significantly increased the production of TNF-α as previously described [30, 31]. In agreement with the present study, stimulation of purified canine polymorphmononuclear cells (PMNs) with lipoteichoic acid, a ligand of TLR2, promoted the release of pro-inflammatory chemokine IL-8 [32].…”
Section: Discussionsupporting
confidence: 92%
“…Further studies investigating the interactions of E. faecium with prebiotics and other substances should be encouraged, as this might help to understand its role as a probiotic in veterinary medicine. So far, clinical trials with E. faecium as a probiotic with our without prebiotics have not been encouraging which might partially be due to the fact that likely high numbers of this strain are needed in vivo to elicit an effect (personal observations of the authors), but also potentially because a way to enhance E.faecium growth in vivo and in vitro have not yet been identified in these scenarios [3][4][5]. In only one study that was assessing the effect of another probiotic formulation; an increase in faecal enterococci was observed in dogs [22].…”
Section: Resultsmentioning
confidence: 99%
“…They are popular for the treatment of several conditions in small animals, mostly related to the gastrointestinal (GI) tract, where there is some evidence that they can alleviate symptoms of acute gastroenteritis [1,2]. There have also been several attempts to assess potential health benefits of probiotics in chronic GI conditions in small animals [3][4][5][6]. Even though a probiotic is defined as "a live organism which, if administered in adequate quantities, confers a health benefit to the host" proof of efficacy in specific conditions is often lacking, as most of these products are sold as health/ food supplements, not as drugs [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Schmitz et al studied the dog's duodenal biopsies and whole blood and demonstrated that E. faecium stimulated the expression of pro-inflammatory cytokines including IL-17A, IL-22, Interferon gamma (IFN-γ) and TNF-α in the duodenal biopsies and serum and subsequently enhanced the immune responses against pathogens. 21 The probiotic form of E. faecium (NCIMB 10415) also increased the production of NO by the phagocyte cells of pigs. 22 Based on the results, it appears that E. faecium modulates the innate immunity to fight against pathogens.…”
Section: Enterococcus Faecium and Its Effects On The Immune Responsesmentioning
confidence: 99%